2016
DOI: 10.1177/0886260516628292
|View full text |Cite
|
Sign up to set email alerts
|

Does Who You Know Affect How You Act? The Impact of Relationships on Bystander Intervention in Interpersonal Violence Situations

Abstract: This study utilized an experimental design to determine how bystanders would intervene in campus sexual assault (SA) or intimate partner violence (IPV) situations. Specifically, it examines whether the type of intervention (direct, indirect, or delegation) is associated with relational distance, the nature of the crime, or the sex of the bystander. A random sample of college students completed a web-based survey at a private university in the Midwest. Survey participants were randomly assigned two vignettes-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 44 publications
7
33
0
Order By: Relevance
“…This study also found that the method of intervention bystanders chose was different for sexual assault and partner violence (Weitzman et al, 2017). Furthermore, a study among college students showed that men had the highest probability of directly intervening in sexual assault, whereas women had the highest probability of indirectly intervening in partner violence (Palmer, Nicksa, & McMahon, 2018). Results also showed that students who knew neither the victim nor the perpetrator tended to choose to delegate the intervention to someone else (Palmer et al, 2018).…”
Section: Bystander Interventions For Preventing Tdvmentioning
confidence: 99%
“…This study also found that the method of intervention bystanders chose was different for sexual assault and partner violence (Weitzman et al, 2017). Furthermore, a study among college students showed that men had the highest probability of directly intervening in sexual assault, whereas women had the highest probability of indirectly intervening in partner violence (Palmer, Nicksa, & McMahon, 2018). Results also showed that students who knew neither the victim nor the perpetrator tended to choose to delegate the intervention to someone else (Palmer et al, 2018).…”
Section: Bystander Interventions For Preventing Tdvmentioning
confidence: 99%
“…Indeed, a number of researchers have begun to expand our investigation of bystander behavior in important ways. For example, some studies ask not only whether students engage in bystander behavior but also ask separately about acquaintances, friends, and strangers (Banyard et al, 2014; Katz & Nguyen, 2016; Nicksa, 2011; Palmer, Nicksa, & McMahon, 2016), and whether bystanders would react differently if the types of victimization varied (Banyard, Weber, Grych, & Hamby, 2018; Palmer et al, 2018).…”
Section: Measuring Bystander Behaviorsmentioning
confidence: 99%
“…The broad range of targeted behaviors obscures the success of sexual assault prevention. In addition, bystander behaviors assessed may be specific to friends who elicit greater empathy [ 27 , 30 , 38 ] with unknown generalizability to acquaintances or strangers.…”
Section: Challenges Of Operationalizing Bystander Actionmentioning
confidence: 99%